Age- and sex-specific dermal exposure of polycyclic aromatic hydrocarbons in the general population of a city in south China. (1st October 2022) - Guo, Jian; Luo, Xiaojun; Yang, Yan; Lv, Yinzhi; Zeng, Yanhong; Mai, Bixian
Abstract: This study assessed the dermal exposure of population to polycyclic aromatic hydrocarbons (PAHs) in a South China city. Skin wipe samples of the face, hand, forearm, and shank were collected from 120 volunteers (50% male and 50% female) belonging to different age groups (preschooler, thresholder, middle-aged, and elderly). Concentrations of PAHs in the skin wipe samples varied from 18 to 27000 ng/m 2 in the order of face > hand > forearm > shank, regardless of age and gender. The PAH concentrations of bare skin locations were significantly higher in females than in males, while no significant differences were observed for clothing-covered skin locations between genders. The PAH concentrations for faces were significantly higher in the elderly compared to the other groups. The PAH composition was distinct between the four age groups. The dermal exposure levels of total PAHs and total BaP equivalent concentration (BaPeq ) varied from 25.6 to 620 and 0.093–37.4 ng/kg body weight/d, respectively. The dermal exposure levels of total PAHs were significantly higher in females than in males in all age groups except for the middle-aged group. The hand-mouth exposure doses were significantly higher in the preschoolers than in the other age groups. The values of the carcinogenic risk caused by dermal PAH exposure were between 3.5 × 10 −6 and 1.4 × 10 −3 with 29% of the population (35/120) having risk values exceeding significant levels (1 × 10 −4 ). The thresholder group exhibited the highest risk for PAH dermal exposure among all groups of the population. This study provides a comprehensive evaluation of the age- and gender-related risk of PAH through dermal exposure. Graphical abstract: Image 1 Highlights: PAH concentrations in skin follow the order: face>hand>arm>leg. PAH concentrations and compositions were age- and gender-specific. Cancer risk of 29% of study population exceeded significant levels.